Beyond Becquerel and Biology to Precision Radiomolecular Oncology: Festschrift in Honor of Richard P. Baum (Cham Springer Nature, 2024)
This open access book is written by world-renowned experts on radiomolecular precision oncology to celebrate the work, life, principles and ideology of Richard P Baum. It includes commentaries, reviews and some thought provoking novel ideas on radionuclide precision oncology, covering topics such as various aspects of theranostics and molecular radiotherapy like radiolabeled peptides, radiolabeled antibodies, dosimetry, and quality control as well as the diagnosis and treatment of specific tumor types. Featuring contributions by biologists, physicists, chemists, mathematicians, geneticists, and physicians from a range of specialties, this Festschrift is highly interdisciplinary and will be a valuable resource for future precision oncologists.
English
Keywords: Clinical and internal medicine; Medical physics; Nuclear medicine